Practicality test of SaLDI biology learning model integrated with TPACK on biology materials - Suhardi Aldi; Adnan Adnan; Andi Asmawati Azis (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
The existing learning models in biology education still have limitations in practically integrating technology, pedagogy, and content, often resulting in passive student learning and suboptimal critical thinking development. Therefore, it is necessary to explore and test the feasibility of biology learning models, specifically TPACK-integrated SaLDI biology learning model, in creating active and student-centred biology learning that aligns with the demands of the 21st century. The purpose of this study was to test the practicality of the SaLDI learning model integrated with TPACK. This type of research is descriptive quantitative which tests the practicality of the TPACK-integrated SaLDI biology learning model. The population in this study were all students and teachers who participated in Biology learning at SMAN 14 Makassar which became the research location. The sampling technique used was random sampling, as many as 32 students and 2 teachers. The instrument used was student and teacher response questionnaire. The instrument that has been developed is used to collect data on the practicality of the TPACK-integrated SaLDI biology learning model. The data generated was then analysed quantitatively. Based on the results of the study, it can be seen that the practicality of the TPACK-integrated SaLDI learning model, as viewed from the perspective of teachers and students, is very practical. The conclusion of this study is that this learning model is very practical to use by teachers and students. This practicality encourages more effective, interactive, and adaptive Biology learning. The suggestion of this research is that it is still necessary to test the implementation of the TPACK-integrated SaLDI learning model on a wider scale.Abstrak. Model pembelajaran yang ada dalam pendidikan biologi masih memiliki keterbatasan dalam mengintegrasikan teknologi, pedagogi, dan konten secara praktis, seringkali mengakibatkan pembelajaran peserta didik yang pasif dan pengembangan pemikiran kritis yang kurang optimal. Oleh karena itu, perlu untuk mengeksplorasi dan menguji kelayakan model pembelajaran biologi dalam hal ini adalah SaLDI yang terintegrasi dengan TPACK dalam menciptakan pembelajaran biologi yang aktif dan berpusat pada peserta didik sesuai dengan tuntutan abad ke-21. Tujuan dari penelitian ini adalah untuk menguji kepraktisan model pembelajaran SaLDI terintegrasi TPACK. Jenis penelitian ini adalah kuantitatif deskriptif yang menguji kepraktisan model pembelajaran Biologi SaLDI terintegrasi TPACK. Populasi dalam penelitian ini adalah seluruh peserta didik dan guru yang mengikuti pembelajaran Biologi di SMAN 14 Makassar yang menjadi lokasi penelitian. Teknik pengambilan sampel yang digunakan yaitu random sampling, sebanyak 32 peserta didik dan 2 guru. Instrumen yang digunakan adalah angket respon peserta didik dan guru. Instrumen yang telah dikembangkan digunakan untuk pengumpulan data kepraktisan model pembelajaran Biologi SaLDI terintegrasi TPACK. Data yang dihasilkan kemudian dianalisis secara kuantitatif. Berdasarkan hasil penelitian menggambarkan bahwa tingkat kepraktisan model pembelajaran SaLDI terintegrasi TPACK ditinjau dari kepraktisan guru dan peserta didik tergolong sangat praktis. Kesimpulan penelitian ini yaitu model pembelajaran ini sangat praktis digunakan oleh guru dan peserta didik. Kepraktisan ini mendorong pembelajaran Biologi yang lebih efektif, interaktif, dan adaptif. Saran penelitian ini yaitu masih perlu menguji implementasi model pembelajaran SaLDI terintegrasi TPACK pada skala lebih luas.